2013
DOI: 10.1128/jvi.00692-13
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Prion Infectivity in Fixed Heart Tissue from Patients with Creutzfeldt-Jakob Disease or Amyloid Heart Disease

Abstract: In most forms of prion disease, infectivity is present primarily in the central nervous system or immune system organs such as spleen and lymph node. However, a transgenic mouse model of prion disease has demonstrated that prion infectivity can also be present as amyloid deposits in heart tissue. Deposition of infectious prions as amyloid in human heart tissue would be a significant public health concern. Although abnormal disease-associated prion protein (PrP Sc ) has not been detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…The sensitivity of tg66 mice to transmission of human sCJD and vCJD was reported previously [ 37 , 38 ], and this sensitivity was emphasized in the present study by the transmission of infectivity from Y226X brain obtained from formalin-fixed tissue sections which were removed from microscope slides. Previous experiments have shown that prion infectivity is only partially sensitive to treatment with formalin [ 40 ], and can be obtained from formalin-fixed brain [ 2 , 15 , 32 , 35 ]. In the case of Y226X, formalin-fixed brain was the only tissue available, even in the initial description of this patient [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of tg66 mice to transmission of human sCJD and vCJD was reported previously [ 37 , 38 ], and this sensitivity was emphasized in the present study by the transmission of infectivity from Y226X brain obtained from formalin-fixed tissue sections which were removed from microscope slides. Previous experiments have shown that prion infectivity is only partially sensitive to treatment with formalin [ 40 ], and can be obtained from formalin-fixed brain [ 2 , 15 , 32 , 35 ]. In the case of Y226X, formalin-fixed brain was the only tissue available, even in the initial description of this patient [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established protocols for the isolation of disease associated prion proteins from formalin-fixed paraffin-embedded tissue sections 8 9 10 . Transgenic mice expressing hamster PrP C intracerebrally inoculated with prions isolated from formaldehyde fixed paraffin-embedded 263K scrapie strain terminal brains developed clinical disease 8 .…”
mentioning
confidence: 99%
“…Previous studies have established protocols for the isolation of disease associated prion proteins from formalin-fixed paraffin-embedded tissue sections 8 9 10 . Transgenic mice expressing hamster PrP C intracerebrally inoculated with prions isolated from formaldehyde fixed paraffin-embedded 263K scrapie strain terminal brains developed clinical disease 8 . Prion protein can be demonstrated in some archived formalin-fixed paraffin-embedded tissues and detected by western blotting, albeit with lower levels of sensitivity, typically limiting this method to terminal samples 9 10 .…”
mentioning
confidence: 99%
“…The presence of amyloid plaques was confirmed by staining deparaffinized sections with the amyloid dye Thioflavin S (ThioS) as previously described [35]. Hamotoxylin and eosin (H&E) staining was performed by hand on deparaffinized slides using Shandon Instant Hemotoxylin and Eosin (Thermo Scientific) according to the manufacturer's instructions.…”
Section: Other Stainsmentioning
confidence: 99%